Sex Estimation Using Radiographic Films of the Frontal Sinuses in Thai Populations - ์Ngamnusonkit Bandhit; Vachirawongsakorn, Vijarn (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aims to determine the forensic importance and applicability of the frontal sinus by evaluating its morphoscopic and morphometric characteristics in relation to sex. Methods Antero-posterior skull radiographs of 235 individuals (141 males and 94 females) were taken using a standardized procedure. Frontal sinus morphology was observed and classified. Specific measurements (A to D) were conducted to estimate sex by developing logistic regression equations. Results Frontal sinus symmetry was detected in 58.7% of the indivi-duals. Morphometric analyses of frontal sinuses were only moderately correlated with the sex, with an area under the ROC curve of 0.629 (measurement A). The recommended cut-off score of measurement A was 6.47 cm, in which the sensitivity and specificity were 78.7% and 59.6%, respectively. Conclusions This study found significant individual variation in the frontal sinus patterns. Evaluating the frontal sinus could be used as an adjunct to other methods of personal identification, particularly for sex estimation.